The association between calfhood BRDC and subsequent departure from the herd, milk production, and reproduction: an observational, retrospective study - Schaffer, Aaron P. (Kansas State University, 2013)
Bovine respiratory disease (BRDC) is a multifaceted disease that causes considerable economic loss in both the beef and dairy industry. However, because there may be lingering effects of BRDC in the dairy industry, the full economic costs of the disease may not be realized. These lingering effects may include an increased departure from the herd, decreased milk production, and decreased reproductive performance. All of these outcomes are affected by multiple variables, but proper statistical modeling can control for many of the different influences. Few studies have attempted to look at the long term effects of calfhood BRDC but consistent associations have not been identified. The objective of this observational, retrospective study was to determine the association between calfhood BRDC prior to 120 d of age and departure from the herd, milk production, and reproductive performance. The association between the occurrence of BRDC with departure from the herd prior to first calving depended on the birth year, but for 5 of the 6 years, animals that contracted BRDC were 1.62 to 4.98 times more likely to leave the herd than animals that did not contract BRDC. In addition, animals that contracted BRDC were also 1.28 times more likely to leave the herd between first and second calving than animals that did not contract BRDC. Furthermore, the age at BRDC occurrence was associated with departure from the herd. Animals that contracted BRDC pre-weaning were 2.62 times more likely to leave the herd prior to first calving than animals that contracted BRDC post-weaning. However, age of BRDC occurrence was not significantly associated with departure from the herd between first and second calving. The occurrence of BRDC during the first 120 d of life was associated with a 233 kg decrease in lactation-one production, but was not significantly associated with production in subsequent lactations. Finally, calfhood BRDC was not significantly associated with a decreased reproductive performance measured by calving interval. In conclusion, calfhood BRDC negatively impacts productivity both prior to and after first calving.
Keywords: Dairy calfBovine respiratory disease; Departure from the herd; Milk production; Animal Diseases (0476); Veterinary Medicine (0778)